Applications of open source software in land administration: An initiation with land administration education - Bhatta, Ganesh Prasad (Journal on Geoinformatics, Nepal, 2009)
The LA System in Nepal is quite traditional. The government has realized the need of modernizing the system and some positive efforts are underway at the moment. Introduction of Geo-ICT in the business system is one of the main objectives of these efforts. Capacity building is an essential aspect to be considered before introducing modernisation in the system. Some efforts are underway in this aspect such as human resource development through Geomatic Education in the country. Recently, Kathmandu University (KU) has introduced a bachelor’s degree level course in Geomatics Engineering, i.e. Bachelor’s of Engineering (B.E.) on Geomatics, as a collaborative program with Land Management Training Center (LMTC). This new initiative would include Geo-ICT based land administration education. Application of Open Source Software (OSS) for the education could be a better choice for KU and LMTC to exploit all possible functionalities of the OSS in developing / supporting a Geo-ICT based land administration education With this ground, the author carried out a study to overview the possibilities with Open Source Software (OSS) to apply for land administration in Nepal. The paper is developed out of the study.